Impact of Interest Loan, Growth of Regional Gross Domestic Product, Inflation and Economic Growth on Loans at Credit Union in West Kalimantan, Indonesia - Maran, Maran (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
Loans or credits offered by Kopdit credit unions are a potential source of funds that need to be developed, to help accelerate the home industry and the micro and small economies. Therefore, we want to see the impact of several conditions such as the loan interest rate, GDP per capita growth, inflation rate and economic growth. Quite a number of studies have looked at the impact of interest rates, GDP growth, inflation rates and economic growth on loans or credits to banks or banking institutions. We do not look at credit or loans from banks, but on Kopdit credit unions (CU). The results of our research show that simultaneously the loan interest rate, GDP growth, inflation rate and economic growth have a strong enough influence on loans at Credit Union Credit Unions, namely 79.2454%. Partially the variable of loan interest rate, GDP growth per capita, inflation rate affects outstanding loans, while economic growth partially has no effect on outstanding loans.